Vertical coordination in high-value commodities: implications for smallholders - Birthal, Pratap Singh; Joshi, Pramod Kumar; Gulati, Ashok (International Food Policy Research Institute, 2005)
Rising per capita income, urbanization and globalization are changing the consumption basket in the developing countries towards high-value commodities (like fruits & vegetables, milk, meat, poultry, fish, etc.). This paper explores how smallholders can benefit from the emerging opportunities from a silent demand-driven changes in high-value agriculture in India. The study examines the institutional mechanisms adopted by different firms to integrate small producers of milk, broilers and vegetables in supply chain and their effects on producers’ transaction costs and farm profitability. The study finds that the innovative institutional arrangements in the form of contract farming have considerably reduced transaction costs and improved market efficiency to benefit the smallholders. The study does not find any bias against smallholders in contract farming. Also, the study does not find that the relevant firms have exploited their monopsonistic position by paying lower prices to farmers. On the contrary, contract producers were found enjoying benefits of assured procurement of their produce and higher prices. The study lists policy hurdles in scaling up the innovative models of vertical coordination in high-value food commodities